Respuesta :
Answer:
x = 10,-4
Step-by-step explanation:
(x-3)^2 -49 = (x-3-7)(x-3+7)
= (x-10)(x+4)
The zeros of f(x) are 10 ,-4
What is Expansion?
- An expansion of a product of sums expresses it as a sum of products by using the fact that multiplication distributes over addition
How to Solve this Problem?
This problem can be solved by following steps
- The given equation is equal to zero
- Expand (x-3)^2
- Split the middle term
- Take the common factors
- And find out the zeros of the equation
[tex]f(x)=0\\(x-3)^{2}-49=0\\ x^{2} -6x-40=0\\x^{2} -10x+4x-40=0\\x(x-10)+4(x-10)\\(x-10)(x+4)\\x = 10 , -4[/tex]
Hence the zeroes are 10 and -4
Learn more about zeroes here
https://brainly.com/question/10629698
#SPJ2